2011
DOI: 10.1111/j.1365-3024.2011.01310.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of scuticociliate proteinases in infection success in turbot, Psetta maxima (L.)

Abstract: Scuticociliatosis caused by Philasterides dicentrarchi is one of the most severe diseases of farmed turbot, Psetta maxima (L.). Immunized fish showed elevated levels of specific antibodies (Ab), which caused the destruction of parasites through the activation of complement by the alternative and classical pathways. By using affinity chromatography on bacitracin-sepharose columns, we demonstrated the existence of high levels of parasite proteinases in the serum and, to a lesser extent, in the ascitic fluid of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…Proteolytic enzymes generated by parasites are often involved in such processes, as studied for the myxozoans Kudoa sp. (Martone et al 1999, Funk et al 2008, Myxobolus cerebralis (Kelley et al 2004, Dörfler & El-Matbouli 2007 and Sphaerospora dicentrarchi (Muñoz et al 2000a), as well as for other piscine parasites (Zuo & Woo 1998, Paramá et al 2004, Piazzón et al 2011. There is no current knowledge about the mechanisms that Enteromyxum leei employs to disrupt cell junctions between enterocytes, to penetrate and invade the intestinal epithelium and to migrate along the digestive tract.…”
Section: Introductionmentioning
confidence: 96%
“…Proteolytic enzymes generated by parasites are often involved in such processes, as studied for the myxozoans Kudoa sp. (Martone et al 1999, Funk et al 2008, Myxobolus cerebralis (Kelley et al 2004, Dörfler & El-Matbouli 2007 and Sphaerospora dicentrarchi (Muñoz et al 2000a), as well as for other piscine parasites (Zuo & Woo 1998, Paramá et al 2004, Piazzón et al 2011. There is no current knowledge about the mechanisms that Enteromyxum leei employs to disrupt cell junctions between enterocytes, to penetrate and invade the intestinal epithelium and to migrate along the digestive tract.…”
Section: Introductionmentioning
confidence: 96%
“…It has been reported that peptidases secreted by Philasterides dicentrarchi can degrade type-I collagen, modulate host cellular immune responses, and induce apoptosis of leucocytes [8-11]. Moreover, P. dicentrarchi peptidases could affect host humoral immune responses by degrading the host immunoglobulins and reducing host complement activity in fish serum and ascitic fluid [12]. …”
Section: Introductionmentioning
confidence: 99%
“…However complement that was activated through the classical pathway was a potent killer of M. avidus [159,160]. These results suggested that the humoral responses were more important than cellular immune responses in defense against M. avidus [161,159].…”
Section: Host Responsesmentioning
confidence: 90%
“…The avirulent Tet-NI 1 had no cysteine protease activity, whereas the virulent Tet-NI 6 had high levels of activity. Cultures of M. avidus have been used as source of proteinases and a way of evaluating the killing activity of sera from fish that had or had not been injected with the ciliate [158,161]. Through activation of the classical complement pathway, serum from vaccinated turbot killed M. avidus in culture [160,161].…”
Section: Pathogenic Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation